The feasibility of tropical pitcher plant (Nepenthes sp.) exploration booklet as a learning media - Syaiful Azhar; Melfa Aisyah Hutasuhut (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
Learning media is designed to arouse curiosity and increase students' knowledge. If only listening to verbal information from the teacher, students are more likely to ignore what is being taught. Therefore, the use of learning media has proven to be effective. Currently, learning materials are sourced from textbooks. This study aims to determine the feasibility, practicality, and effectiveness of a booklet developed from the inventory of pitcher plants (Nepenthes sp.) as a learning medium for high school/MA students. The research stages include the needs analysis stage, the booklet planning stage, the booklet creation stage, the validation stage, the trial stage, and the multiplication of booklet prints. The research instruments are in the form of validation sheets and questionnaires. Material experts and design experts assess validation. The practical tests of students and teachers include evaluating the booklet's physical appearance and overall content. The validation assessment was 88.6% and 90.4%